MORFOMETRI DAN KARAKTERISTIK FISIK TUMISI (Amphidromus peversus) DARI KAMPUS UNIVERSITAS UDAYANA BUKIT JIMBARAN, BALI-INDONESIA - Sudatri, N. W.; Suartini, N. M.; Raka Dalem, A. A. G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
A study on mollusks (Amphidromus peversus) has been carried out on Udayana University, BukitJimbaran (Bali, Indonesia) campus between November, 2003- November, 2005. The study was undertakenon a secondary forest on a limestone dry soil with dominant vegetation of Glerecydium sepium, Lantanacamara, Ceiba pentranda, and Acasia auriculiformis. Samples were randomly taken on quadrate samplings.Mollusks were captured on the land surface or on living vegetations. Results of the study showed that A.peversus has an average of shell length of 27.9 mm, shell width 18.0 mm , and body weight 7.90 g, number ofshell whorls 5.3, with the proportion of direction of whorl to the right of 55.3%. The shell of A. peversus hasno operculum. The color of the shell was yellow with brown stripes.The relationship between shell length (X) and with body weight (Y) can be represented by theequation of Y = 0.473 X – 5.32 (R2 = 11.9 %), which showed week relationships between those parameters.Meanwhile the relationships between the shell length (X1), width (X2) and body weight (Y) was best fitted bythe following equation : Y = 0.289 X1 + 0.0140 X2 – 3.47 (R2 = 94.9%).
Keywords: Amphidromus peversus, morphometry, shell, relationship, Bali